Capitalising on administrative data to innovate and drive evaluation excellence - Gracey, Faye; Davies, Hannah (International Journal of Population Data Science, 2026)
Administrative Data Research (ADR) is transforming evaluation practice by improving robustness, complementing more traditional methods, and enabling evidence-based decision-making. In Wales, ADR Wales has embedded administrative data linkage into all Welsh Government evaluability assessments as standard practice, ensuring evaluations consider these rich data sources. Through the Secure Anonymised Information Linkage (SAIL) Databank, more Welsh population-level administrative data is available in Trusted Research Environments (TREs) that can be linked together, creating opportunities for evaluators to innovate. ADR Wales—a partnership between Welsh Government, Swansea University Medical School, and WISERD at Cardiff University—has demonstrated the value of linked data to Ministers and policy colleagues by informing evaluations of major initiatives, including early years interventions, the 20mph speed limit legislation, the basic income pilot for care leavers, tertiary education reform, and much more. Working alongside the UK Evaluation Society and the UK Evaluation Taskforce, ADR Wales is helping to mainstream administrative data use across the ADR UK network. This work improves evaluation quality, delivers value for money, and has a direct impact on citizens’ lives. Supported by UK Research and Innovation and the ESRC, our renewed five-year funding will strengthen collaboration and expand data linkage opportunities. This session will showcase Welsh innovations in linked ADR, highlight practical strategies for integrating administrative data into evaluation design, using administrative data to complement other evaluation methods, and share lessons on how to encourage data owners (e.g. police, local authorities, and the third sector) to share data in TREs to unlock future evaluation potential.